2017
DOI: 10.23736/s0393-2249.17.02838-7
|View full text |Cite
|
Sign up to set email alerts
|

Extended versus standard pelvic lymphadenectomy during robot-assisted radical prostatectomy: the role of extended template as an independent predictor of lymph node invasion with comparable morbidity burden

Abstract: MiNerVa Urologica e Nefrologica 475 precise prognosis and helping in the decision making process for the selection of either adjuvant or salvage therapy.Until nowadays, the indication to perform i n the treatment of prostate cancer (Pca), pelvic lymph node dissection (PlND) represents the most effective method to diagnose lymph node invasion (lNi), allowing a more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…A total of 70.6% of patients, including 876 (56.9%) patients with low/intermediate‐risk PCa and 957 (82.4%) with high‐risk PCa, underwent PLND (Table 2). In addition, the range of lymphadenectomy was extended in 317 patients (16.8%), standard in 247 (13.1%), and limited in 1322 (70.1%) 17,18 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 70.6% of patients, including 876 (56.9%) patients with low/intermediate‐risk PCa and 957 (82.4%) with high‐risk PCa, underwent PLND (Table 2). In addition, the range of lymphadenectomy was extended in 317 patients (16.8%), standard in 247 (13.1%), and limited in 1322 (70.1%) 17,18 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the range of lymphadenectomy was extended in 317 patients (16.8%), standard in 247 (13.1%), and limited in 1322 (70.1%). 17,18 RARP-related perioperative complications were identified in 198 patients (7.4%), including 69 patients (2.6%) with grade 3/4 complications according to the Clavien-Dindo classification (Table 3). The most common surgery-related complication in this study was urinary leakage at the urethrovesical anastomosis.…”
Section: Surgical Outcomesmentioning
confidence: 99%
“…Different studies have demonstrated that extended PLND (ePLND) provides better pathological staging in PC compared to limited PLND (lPLND) or standard PLND (sPLND). [22][23][24] Therefore, present guidelines recommend ePLND if PLND is being considered.…”
Section: Discussionmentioning
confidence: 99%